LEGAL PROTECTION AGAINST STUDENTS VICTIMS OF CRIMINAL ACTIVITIES - Meilani, Linda; Putri, Djuwiah Putri; Rusmansyah, Moch (IBLAM LAW REVIEW, 2022)
This journal is entitled Protection of Santriwati Victims of the Crime of Obscenity (Case Study: Herry Wirawan) The background behind the writing of this journal is that there is a pesantren leader who is in the wildlife foundation complex, Cibiru sub-district, Bandung City who commits sexual abuse against his female students who are still as a child, where this santriwati (child) must be given a protection both physically and emotionally for the child, as regulated in Law no. 35 of 2014 concerning Child Protection. The purpose of writing this journal is to find out how the legal protection for female students who are victims of criminal acts of abuse and legal remedies for the protection of female students as victims of criminal acts of obscenity is.